GOVERNMENT SUPPORT FOR ENTREPRENEURSHIP IN DEVELOPED COUNTRIES AND ADAPTATION OF EXPERIENCE IN THE REPUBLIC OF UZBEKISTAN - Rakhmatjanov Lazizkhan Turabayevich, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract: The article examines the foreign experience of state support of small business  in  the  largest  foreign  countries.  The  mechanisms  of  development  of  state support for small business in foreign countries are considered, the analysis of the level of development of small business in foreign countries and the Republic of Uzbekistan is given. The main directions and program activities on this issue have been identified and  analyzed.  The  high  socio-economic  orientation  of  small  and  medium-sized businesses was noted.